The Impact of Canadian Training Programs on Long Term Unemployed - Geehan, Randall; Swimmer, Gene (Relations industrielles / Industrial Relations, 1991)
The purpose of this paper is to develop an econometric model capable of correcting the selection bias resulting from any simple comparison between participants and non-participants to training programs. It also aims at estimating the incremental impact of three Canadian training programs aimed at the long term unemployed.